Analisis QoS Pada Smart Garden Berbasis IoT Dengan Protokol MQTT Menggunakan Wireshark - Muhammad Syafaat Faat; Furqan Zakiyabarsi Furqan; Furqan Zakiyabarsi fizar (Jurnal INSYPRO (Information System and Processing), 2022)
In early 2020 the world was hit by an outbreak of Coronavirus disease 2019 (COVID-19). This has led to the implementation of PPKM (Enforcement of Restrictions on Community Activities) in Indonesia, so that people are faced with conditions where more activities are carried out around the house. For people who do urban farming by taking advantage of narrow land conditions around residential areas or Urban Farming is an option to fill activities at home. However, along with the easing of the PPKM rules, the community also returned to their normal activities so that the plants that used to grow well were no longer due to the people being treated returning to work or activities in the office, so a technological solution was created that could help the community to monitor and control their plants even though remotely, namely by utilizing a tool designed, namely the Smart Garden based on the Internet of Things. The purpose of this study is to analyze the quality of data transmission on a device designed with several QoS (Quality of Services) parameters. The results of the tests carried out by the designed tool succeeded in sending data from the sensor to the Adafruit.IO webserver by utilizing the MQTT (Message Queuing Telemetry Transport) protocol so that an analysis of QoS can be carried out with the throughput results having an average value of 892,725 kbps in the medium category so that the value the index is 2, the average packet loss value is 0.01% with the satisfactory category so the index value is 4, the average delay value is 232.4923 m/s with a good category so the index value is 3, and the average jitter value is 226.9191 m /s so the category is bad so the index value is 1.